VD_FINDINFO Jug / 2010 / 31 vom 9. April 2010 - VD Tribunal cantonal (2010)
DIVORCE, PARTAGESENS GÉNÉRAL, PRÉVOYANCE PROFESSIONNELLE | 122 al. 1 CC, 142 al. 2 CC, 22 LFLP, 8a OLP, 12 OPP2, 110 al. 1 LPA-VD, 111 al. 1 LPA-VD